BUDAYA RITUAL SANTRI DALAM PEMBENTUKAN RESILIENSI AKADEMIK DI PONDOK PESANTREN NURUL ISLAM KARANGJATI SAMPANG - Zahwa Aprilita; Muh Hanif (Kampus Akademik Publiser, 2026)
Abstract. The daily life of students at boarding schools follows a structured and rigorous routine, including congregational prayer, Quran recitation, and evening study sessions, which not only foster discipline but also play a role in building the students’ academic resilience. This study aims to analyze the role of daily rituals in fostering academic resilience among students at the Nurul Islam Islamic Boarding School in Karangjati, Sampang. The research employs a qualitative approach using observation, interviews, and documentation. The findings indicate that daily rituals foster students’ discipline, physical, and mental resilience through the habit formation of structured activities. Group activities also foster social solidarity, which helps students cope with academic pressure, fatigue, and homesickness. Students perceive worship and routines as sources of spiritual strength to endure academic demands. Thus, daily rituals in Islamic boarding schools serve not only as religious practices but also as social mechanisms in fostering academic resilience and strengthening students’ character within the Islamic educational environment. Keywords: daily rituals; boarding school students; academic resilience; residential Islamic boarding schools; solidarity. Abstrak. Kehidupan santri di pesantren berasrama memiliki ritual harian yang teratur dan padat, seperti salat berjamaah, mengaji, dan belajar malam, yang tidak hanya membentuk kedisiplinan tetapi juga berperan dalam membangun ketahanan akademik santri. Penelitian ini bertujuan menganalisis peran ritual harian dalam pembentukan resiliensi akademik santri di Pondok Pesantren Nurul Islam Karangjati Sampang. Penelitian menggunakan pendekatan kualitatif dengan teknik observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa ritual harian mampu membentuk disiplin, ketahanan fisik, dan mental santri melalui pembiasaan aktivitas yang terstruktur. Kegiatan bersama juga menciptakan solidaritas sosial yang membantu santri menghadapi tekanan belajar, kelelahan, dan rasa rindu rumah. Santri memaknai ibadah dan rutinitas sebagai sumber kekuatan spiritual untuk bertahan dalam tuntutan akademik. Dengan demikian, ritual harian di pesantren tidak hanya berfungsi sebagai praktik keagamaan, tetapi juga sebagai mekanisme sosial dalam pembentukan resiliensi akademik dan penguatan karakter santri di lingkungan pendidikan Islam. Kata Kunci: ritual harian; santri; resiliensi akademik; pesantren berasrama; solidaritas.